TAZ ameliorates the microglia-mediated inflammatory response via the Nrf2-ROS-NF-κB pathway - Ji-Cheng Huang; Zhan-Peng Yue; Hai-Fan Yu; Zhan-Qing Yang; Yu-Si Wang; Bin Guo (Elsevier, 2022)
Transcriptional co-activator with PDZ-binding motif (TAZ), one of core modules of the Hippo pathway, involves inflammatory cell infiltration in the liver, but little information is available regarding its physiological function in the microglia-mediated inflammatory response. Here we revealed that activation of TAZ prevented microglia production of proinflammatory cytokines, indicating TAZ's importance in anti-inflammation. After translocation into the nucleus, TAZ interacted with transcriptional enhanced associate domain (TEAD) and bound to the promoter of nuclear factor erythroid 2-related factor 2 (Nrf2), whose blockage caused inability of TAZ to improve inflammation, implying that Nrf2 is a direct target of TAZ. Further analysis showed that TAZ induced Nrf2 nuclear translocation to enhance antioxidant capacity with attenuation of oxidative stress and the inflammatory response. Under inflammatory conditions, TAZ impeded mitochondrial dysfunction, as indicated by amelioration of ATP levels, mtDNA copy numbers, and mitochondrial membrane potential with an obvious reduction in mitochondrial superoxide, but this impediment was neutralized by blockage of Nrf2. TAZ hindered opening of the mitochondrial permeability transition pore, restrained release of cytochrome c from mitochondria into the cytosol, and was sufficient to rescue microglia from apoptosis dependent on Nrf2. Nrf2 acted as a downstream target of TAZ to repress NF-κB activation by enhancing antioxidant capacity. Collectively, TAZ might ameliorate the microglia-mediated inflammatory response through the Nrf2-reactive oxygen species (ROS)-nuclear factor κB (NF-κB) pathway.